(untitled) (International journal of artificial intelligence, 2025)
Endocrinology, the study of hormones and their physiological effects, plays a central role in the prevention, diagnosis, and treatment of various metabolic and systemic disorders. This article provides a comprehensive overview of the key endocrine disorders, recent diagnostic methods, and therapeutic innovations. It highlights the importance of integrating clinical practice with laboratory advances to improve patient outcomes.